The good fail : entrepreneurial lessons from the rise and fall of Microworkz - Latman, Richard Keith (Hoboken, New Jersey : John Wiley & Sons, Inc., 2012)
'An inside look at how companies and executives rise and fall, with important lessons for all aspiring entrepreneursThe Good Fail is part business story, part guilty pleasure, exploring Richard Keith Latman's very public missteps and the painful lessons he learned as a result, presented to fellow entrepreneurs, in his own words, for the first time. Written in a lively, conversational style, the book answers questions many computer industry veterans have been asking for more than a decade about what went wrong at Microworkz, the failed former free PC enterprise. Chronicling Latman's long roller-coaster journey back and offering pointed advice about effective business development, negotiating, human resource management, and leadership, which Latman has successfully applied at his latest ventures, iMagicLab and Latman Interactive, the book is an important set of insights for entrepreneurs everywhere. Offers 19 practical lessons learned, which can help put other entrepreneurs on the path to success faster Includes invaluable insight into how to overcome even the worst public business failures Provides a behind-the-scenes look from the ultimate insider at an important time in computer industry history Presents a case study of how personal and business lives can negatively impact each other Microworkz's failure can be your success. The Good Fail provides both important insights into how to start a business that will reap rewards, and warnings about how to avoid going astray'--
Keywords: Entrepreneurship; Business failures